A School and a Network: CODATA-RDA Data Science Summer Schools Alumni Survey. (18th February 2021) - Bezuidenhout, Louise; Drummond-Curtis, Sara; Walker, Bridget; Shanahan, Hugh; Alfaro-Córdoba, Marcela
The CODATA-RDA Schools for Research Data Science (SRDS) is a network of schools originating in the RDA in 2016. In 2019 it was recognized as an RDA output. To date, over 400 students from 40 countries have been trained in 10 schools. The majority of these students were postgraduates from low/middle-income countries (LMICs). In contrast to many other data science training approaches, the SRDS schools are designed to be 2-week, disciplinarily-agnostic, residential events where students are introduced to a broad range of tools requisite for efficient and responsible data-centric research. This paper presents the results of a survey carried out on alumni from schools held between 2016 and 2019 (45% response). The results of the survey strongly support the SRDS's long-term goals of facilitating data science training/capacity building within LMICs, and to foster communities of early career researchers (ECRs) conducting responsible and open data science research. The survey results demonstrated that 90% of respondent alumni continued to conduct research and make use of the skills acquired at the SRDS. Modules on open and responsible research and research data management were rated as important for future research. 79% of respondents confirmed that they maintained contact with peers, and 31% had set up academic collaborations with peers and/or instructors. Many had gone on to present content from the schools in their home institutions. The survey results clearly demonstrate the impact of the SRDS, and the value of an expanding network of schools supported by the RDA and CODATA.